ANALISIS KERUSAKAN JALAN BERDASARKAN METODE IRI (INTERNATIONAL ROUGHNEES INDEX) DAN PCI (PAVEMENT CONDITION INDEX) - Sa'dillah, M.; Pandulu, Galih Damar; Basri, Moh Hasan (Fakultas Teknik, Universitas Wiraraja, 2024)
Road is a means of land transportation which in many ways is used by local people to travel, as well as assist local people in their daily activities, roads are also very important in working with finance. ac-tion. Surgical techniques for maintenance of road damage are PCI and IRI. The PCI technique provides data on asphalt conditions at the time the research is directed with a value of 0 to 100. Pavement dam-age in the Wagir District Road section is known that the average road damage conditions are box cracks, crocodile cracks, patches, subsidence, grooves, longitudinal cracks and potholes. The road con-ditions consist of two-way one-lane without a median with a road length of 2100 m, a road width of 5 m, and a shoulder of 1 m. The average PCI value is 72 with very good conditions with the percentage re-sults of 80% good, 13% moderate and 8% bad. While the average IRI value is 8 with moderate condi-tion (ok) and the percentage results are 3% good (good), 63% moderate (ok), 13% lightly damaged (not ok) and 23% severely damaged (poor). By exploring the evaluation of road conditions with PCI and IRI techniques, it can provide an overview or description of road conditions that can be used as an infor-mation base for structuring and implementing road restoration and support. So that the author empha-sizes more is to use the PCI repair method because the accuracy of the data is clearer.